When economic and cultural interests align: the anti-immigration voter coalitions driving far right party success in Europe - Halikiopoulou, D; Vlandas, T (Cambridge University Press, 2020)
This article contests the view that the strong positive correlation between anti-immigration attitudes and far right party success necessarily constitutes evidence in support of the cultural grievance thesis. We argue that the success of far right parties depends on their ability to mobilize a coalition of interests between their core supporters, that is voters with cultural grievances over immigration and the often larger group of voters with economic grievances over immigration. Using individual level data from eight rounds of the European Social Survey, our empirical analysis shows that while cultural concerns over immigration are a stronger predictor of far right party support, those who are concerned with the impact of immigration on the economy are important to the far right in numerical terms. Taken together, our findings suggest that economic grievances over immigration remain pivotal within the context of the transnational cleavage.